Penguatan Solidaritas Sosial Melalui FGD Pada Santri di Pondok Pesantren Waria Al-Fatah Kotagede Yogyakarta - Dyaloka Puspita Ningrum (Universitas Muhammadiyah Semarang, 2021)
The existence of waria is often constructed as a marginal group which results in the emergence of discriminatory attitudes in society. On the other hand, the phenomenon that hit the transgender group also intersects with the humanist values of